Illustration and model verification for an inter-cell and intra-cell facility layout problem in a cellular manufacturing system - Ariafar, Shahram; Ismail, Napsiah; Mohd Ariffin, Mohd Khairol Anuar; Say, Hong Tang; Firoozi, Zahra (Trans Tech Publications, 2013)
In a Cellular Manufacturing System (CMS), parts based on their similarities are grouped into part families, and are assigned to one or more machine cells to be manufactured. In the design of a CMS, facility layout problem aims to arrange machine cells in the shop floor and facilities in the machine cells in order to have an efficient layout. In this study, a previously developed cellular layout model will be illustrated and validated for a well-known case from the literature. Lingo optimization software version 12.0 and an enumeration method will be used to solve, and validate the model. The results of this study show the validity of the proposed model.